2022
DOI: 10.1002/hyp.14484
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term suspended sediment and particulate organic carbon yields from the Reynolds Creek Experimental Watershed and Critical Zone Observatory

Abstract: Long‐term (>20 y) suspended sediment (SS) and particulate organic carbon (POC) records are relatively rare and yet are necessary for understanding linkages between climate, erosion and carbon export. We estimated long‐term (>23 y) SS and POC yields from four nested catchments that ranged from <1 to 54 km2 in area across the Reynolds Creek Experimental Watershed and Critical Zone Observatory (RCEW‐CZO) in southwestern Idaho, USA. We found strong relationships between log10SS and log10POC (R2 = 0.38–0.86) that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…These losses were an order of magnitude higher than unburned catchments 36 . Vega et al 25 further showed that the fire response was a two-step process with wind erosion loading leeward (north) aspects preferentially in swales, and these swales were emptied to streams by water erosion 36 . These results again underscore the importance of incorporating multi-scale domains into disturbance models in these regions.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These losses were an order of magnitude higher than unburned catchments 36 . Vega et al 25 further showed that the fire response was a two-step process with wind erosion loading leeward (north) aspects preferentially in swales, and these swales were emptied to streams by water erosion 36 . These results again underscore the importance of incorporating multi-scale domains into disturbance models in these regions.…”
Section: Discussionmentioning
confidence: 79%
“…Other loss pathways not considered in this study but documented in other studies such as wind and water erosional losses may also need consideration in dryland disturbance models. In particular, large losses as sediment and associated particular organic carbon were documented in the two years following the fire, a total of 1.17 and 0.0625 kg m −2 sediment and carbon, respectively 36 . These losses were an order of magnitude higher than unburned catchments 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few parameters (POC, PON, total dissolved Al, Zn, and Ba) did increase with event flows and, for these, it's unclear if fire played a role in the increase or if event flows more generally led to enrichment trends as is common for many non‐fire impacted watersheds (Knapp et al., 2020). For POC and PON specifically, it is likely that fire played a part in generating some of the differences across flow categories due to the close connection between processes mobilizing larger material, like suspended sediment and suspended particulate organic matter, that often leads to strong positive correlations in other watersheds (Glossner et al., 2022; Richardson et al., 2023). In addition, many trace elements are found in association with suspended solids, like organic matter and minerals (Brown & Parks, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The main outlet for Reynolds Creek, Outlet, incorporates streams from the 238 km 2 catchment and includes agriculture areas with flood irrigation and reservoirs. More details on these catchments are described in Glossner et al (2022) and Pierson et al (2001). An irrigation pond, sampled by Souza (2022), collects water from Reynolds Creek and returns irrigation flow prior to the main outlet to be used for additional irrigation within the Reynolds Creek watershed, and it was sampled to determine surface contributions to groundwater recharge at nearby wells.…”
Section: Study Areamentioning
confidence: 99%